Family caregiver burden in schizophrenia: A structural equation model of caregiver, patient, environmental, and family function factors - Sustrami, Dya; Suhardiningsih, AV Sri; Setyowati, Anggi; Fauk, Nelsensius Klau; Arifin, Hidayat (Faculty of Nursing Universitas Padjadjaran, 2024)
Introduction: Families play a critical role in the care and support of individuals with schizophrenia. However, this responsibility often leaves caregivers with significant physical and psychological burdens. Objective: The study aimed to evaluate the family caregiver, patient, environmental factors, and family function as predictors of family caregiver burden in schizophrenia patients. Methods: This study used a cross-sectional design. The population consisted of family caregivers of schizophrenia patients who had experienced at least one episode in the past year, lived in the same house, and had been caregivers for at least one year. We recruited 220 family caregivers of schizophrenia patients. The variables in this study were family caregiver, patient, environmental factors, family function, and caregiver burden. The data was collected using a self-report questionnaire and analyzed using partial least squares. Results: Most respondents were predominantly between the ages of 46 and 65. The model showed that caregiver burden was influenced by the patient factor (t= 4.259, path coefficient: 0.088), environment factor (t= 6.540, path coefficient: 0.288), and family function (t= 10.977, path coefficient: 0.497). These findings showed that family function was the dominant factor in caregiver burden. Conclusion: Patient factors, environmental factors, and family function significantly affected the family caregiver burden, except for the family caregiver factor. This model can help family caregivers decrease their burden by managing family functioning.